STUDI KOMPARASI JUAL BELI DENGAN HAK MEMBELI KEMBALI MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA DAN KOMPILASI HUKUM EKONOMI SYARIAH - Sumardi Sumardi; Rahmat Rahmat; Abu Bakar (Al-Aqad, 2021)
This research seeks to find out the terms of buying and selling with the right to buy back according to the civil law code and according to the compilation of Sharia economic law and know the similarities and differences in the terms of buying and selling with the right to buy back according to the Civil Law Code and the Compilation of Sharia Economic Law. Data analysis technique used by researchers is a systematic interpretation with two steps, namely content analysis and linking between articles related to research. The results of the study showed that buying and selling with the right to buy back according to the Civil Code: The seller was given the right to be able to buy back the goods he had sold under the agreement. In KHES can also occur under the existence of an agreement. The similarities and differences include the right to the buyer to be able to buy back the goods he has sold, equality in the rights and obligations of sellers and buyers, namely sellers both have the right to demand the buyer return the object of sale, and equally obliged to return the original sale price. The rights and obligations of the seller can both demand a return on the purchase price, and the buyer is equally obligated to return the object to the seller. While the difference in provisions in the Civil Code and KHES include